Macromorphological, Anatomical And Molecular Studies Of Some Taxa Of Araliaceae In Egypt (Bangladesh Journal of Plant Taxonomy, 2022)
The present study investigated morphological features, leaf and stem anatomy, leaf architecture, epidermal characteristics, and molecular characters of some taxa of Araliaceae to trace out the diversity and the diagnostic significance of these attributes. The studied taxa based on combination of 260 characters representing 182 morphological and 78 molecular characters which were subjected to a numerical analysis using NTSYSPC program. The generated dendrogram explained the similarities and the differences between the examined taxa. The specific similarities are discussed and compared with some current classification systems. The generated dendrogram from morphological attributes confirmed the separation of Aralieae and Schefflerieae as two tribes of Araliaceae and supported the separation of simple leaved taxa from compound leaved.Bangladesh J. Plant Taxon. 29(2): 283-296, 2022 (December)